Diseño De Prototipo De Vivienda Modular En Barrio Berlin – Localidad De Suba (2022)
The present degree work is focused on the development of a sustainable modular housing architectural system for the Berlin neighborhood of the city of Bogotá. This system seeks to incorporate the concepts of progressive housing and sustainable construction. The Berlin neighborhood is located in the UPZ 71 Tibabuyes sector in the town of Suba de Bogotá. is located on the northwestern side of the city, which, in accordance with article 71 of District Decree 190 of 2004 (Compilation of the POT), has as general guidelines to improve the current infrastructure and consolidate the development of the necessary services to integrate the city with the west of the region, promote urban integration with an emphasis on public space, linked to the recovery of the Juan Amarillo and Jaboque wetlands, likewise, it is part of the area of influence of the Strategic Operation - Centrality of Suba.